2018
DOI: 10.1136/bjophthalmol-2017-311339
|View full text |Cite
|
Sign up to set email alerts
|

Depot-specific characteristics of adipose tissue-derived stromal cells in thyroid-associated orbitopathy

Abstract: ADSCs from different adipose depots of the same donors exhibited similar mesenchymal phenotypes but differed significantly in adipogenic, myofibrogenic potentials and associated HA synthesis. These depot-specific characteristics of ADSCs may contribute to site-specific adipose tissue involvement in TAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As to alcian blue staining, the chondrogenic hMSCs were washed with DPBS three times before the addition of Alcian Blue Cartilage Stain Solution, pH = 1.0 (Solarbio, Beijing, China), the cultures were scanned under a phase contrast microscope (NA 0.75, 20×) after 30 min of incubating and three times of washing. As to Nile red fluorescent staining, the adipogenic induced cells were washed three times and stained with 1 µM Nile red (Solarbio, Beijing, China) with Hoechst 33342 (Solarbio, Beijing, China) for 5 min in room temperature [ 21 ]. After three times of washing, a fluorescence microscope (NA 0.9, 40×, Olympus, Tokyo, Japan) was used for scanning and photography.…”
Section: Methodsmentioning
confidence: 99%
“…As to alcian blue staining, the chondrogenic hMSCs were washed with DPBS three times before the addition of Alcian Blue Cartilage Stain Solution, pH = 1.0 (Solarbio, Beijing, China), the cultures were scanned under a phase contrast microscope (NA 0.75, 20×) after 30 min of incubating and three times of washing. As to Nile red fluorescent staining, the adipogenic induced cells were washed three times and stained with 1 µM Nile red (Solarbio, Beijing, China) with Hoechst 33342 (Solarbio, Beijing, China) for 5 min in room temperature [ 21 ]. After three times of washing, a fluorescence microscope (NA 0.9, 40×, Olympus, Tokyo, Japan) was used for scanning and photography.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported that ADSC therapy could be beneficial in thyroid-associated orbitopathy [117]. It has also been suggested that insulin-like growth factor 1 has proadipogenic and pro-proliferative effects on ADSCs extracted from thyroid-associated ophthalmopathy patients via in vitro studies [118].…”
Section: Potential Applications Of Adipose Stem Cells To Periorbital ...mentioning
confidence: 99%